2006
DOI: 10.1002/bit.20956
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric and kinetic characterisation of Nitrobacter in mixed culture by decoupling the growth and energy generation processes

Abstract: The growth, maintenance and lysis processes of Nitrobacter were characterised. A Nitrobacter culture was enriched in a sequencing batch reactor (SBR). Fluorescent in situ hybridisation showed that Nitrobacter constituted 73% of the bacterial population. Batch tests were carried out to measure the oxygen uptake rate and/or nitrite consumption rate when both nitrite and CO2 were in excess, and in the absence of either of these two substrates. The results obtained, along with the SBR performance data, allowed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 32 publications
3
24
1
Order By: Relevance
“…Heterotrophic bacteria were also included to be able to describe the total biomass concentration since it has been shown that enriched nitrifying systems have a relatively high content of heterotrophic bacteria [18,19] and furthermore, the influent of the real system contained some COD. Six soluble compounds were considered (as concentration in the bulk liquid): total ammonia nitrogen (S TAN ), total nitrite nitrogen (S TNN ), nitrate (S NO 3 ), soluble biodegradable organic nitrogen (S ND ), dissolved oxygen (S O ) and readily biodegradable organic matter (S S ).…”
Section: Model Development and Descriptionmentioning
confidence: 99%
“…Heterotrophic bacteria were also included to be able to describe the total biomass concentration since it has been shown that enriched nitrifying systems have a relatively high content of heterotrophic bacteria [18,19] and furthermore, the influent of the real system contained some COD. Six soluble compounds were considered (as concentration in the bulk liquid): total ammonia nitrogen (S TAN ), total nitrite nitrogen (S TNN ), nitrate (S NO 3 ), soluble biodegradable organic nitrogen (S ND ), dissolved oxygen (S O ) and readily biodegradable organic matter (S S ).…”
Section: Model Development and Descriptionmentioning
confidence: 99%
“…Despite of their differences, heterotrophs and autotrophs coexist in activated sludge in wastewater treatment systems used to remove organic and nitrogen simultaneously. Vadivelu et al (2006) enriched a Nitrobacter culture in a sequencing batch reactor (SBR) fed with nitrite as the sole energy source and bicarbonate as the sole carbon source. Fluorescent in situ hybridization (FISH) showed that Nitrobacter constituted 73% of the bacterial population, suggesting that a great amount of heterotrophs were also present in this nitrifying enriched sludge.…”
Section: Introductionmentioning
confidence: 99%
“…There is less agreement in which direction the rate influences m. Pirt (38) introduced a growth-rate-dependent term for increased maintenance at slower growth. Recent experiments with Nitrobacter growing at maximum rates of 0.02 h Ϫ1 , i.e., similar to those observed with MTBE, supported this model (57). Other examples with Nitrobacter indicated a difference in maintenance requirements for cultures grown in a chemostat as opposed to reactors with biomass retention (55).…”
Section: Discussionmentioning
confidence: 55%